PEMBERDAYAAN PEREMPUAN MELALUI PELATIHAN PEMBUATAN KEMASAN DAN FOTO PRODUK FASHION SEBAGAI UPAYA DI KARANG JOANG BALIKPAPAN UTARA - Supratiwi Amir; Hijriah Hijriah; Hesti Rosita Dwi Putri (Jurnal Abdi Insani, 2023)
This training on making packaging designs and product photos is a continuation of Community Service (PKM) activities to empower mothers in RT 16 Karang Joang. These training participants are sewing training participants who are already capable of producing products, especially clothing. After making fashion products, the participants faced a new problem, namely they did not understand how to market and increase the selling value of the products they made. This empowerment activity aims to provide knowledge and skills in packaging creation and product photography. In particular, people are able to increase the selling value of products so that they attract consumer interest and increase the number of sales. The stages of implementing the activity consisted of the preparation stage where the implementing team conducted a location survey, participant recruitment, and socialization and licensing with the Head of RT 16 Karang Joang. At the implementation stage, the service implementation team provides training and assistance in creating packaging and product photography. The final post-implementation stage is evaluation. Before empowering women, housewives did no other activities apart from cooking, washing and taking care of the house. They do not have special skills to make a living, so they only depend on the income from the head of the family. After attending the training, the participants who are housewives understand the importance of packaging design and photography in marketing. Packaging can add to the selling value of the product, while product photos serve to present the product so that it attracts consumer interest. Participants not only have knowledge but are also skilled at making paper bag and taking product photos using a mobile application. Women's empowerment needs to be carried out continuously through various programs so that they are able to be competitive, entrepreneurship, so as to improve family welfare.